2014
DOI: 10.1016/j.jad.2013.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of manic episodes according to the presence or absence of depressive features as defined in DSM-5: Results from the IMPACT self-reported online survey

Abstract: Bipolar disorder patients with at least 3 depressive symptoms during a manic episode self-reported typical symptomatology. Anxiety with irritability/agitation differentiated patients with depressive symptoms during mania from those with "pure" manic episodes. The results support the use of DSM-5 mixed features specifier and its value in research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
1
42
0
1
Order By: Relevance
“…This proportion is similar to that in the IMPACT survey, where 39.3% of patients self-reported three or more depressive symptoms in a previous manic episode 5. Furthermore, in post hoc analyses of large datasets from randomized, controlled trials in patients with a BD-I manic or mixed episode (DSM-IV or DSM-IV-TR criteria), the proportion of patients meeting proxy criteria for the DSM-5 “with mixed features” specifier was 33.7% (aripiprazole trials), 34.2% (asenapine trials), and 28.0% (olanzapine trials) 10–12…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This proportion is similar to that in the IMPACT survey, where 39.3% of patients self-reported three or more depressive symptoms in a previous manic episode 5. Furthermore, in post hoc analyses of large datasets from randomized, controlled trials in patients with a BD-I manic or mixed episode (DSM-IV or DSM-IV-TR criteria), the proportion of patients meeting proxy criteria for the DSM-5 “with mixed features” specifier was 33.7% (aripiprazole trials), 34.2% (asenapine trials), and 28.0% (olanzapine trials) 10–12…”
Section: Discussionsupporting
confidence: 81%
“…The study also identified a high incidence of anxiety, irritability, and agitation (AIA) symptoms in patients with mixed features (99%, 97%, and 95%, respectively) and a greater severity of AIA symptoms in these patients compared with patients without mixed features 4. Similarly, in the IMPACT online survey, a high proportion of patients experiencing BD-I mania with three or more self-reported depressive symptoms also reported both “anxiety or worry” and “irritability or agitation” (72.4%) 5. Clearly, AIA symptoms are core features of mixed episodes.…”
Section: Introductionmentioning
confidence: 99%
“…The DSM-5 definition of the 'with mixed features' specifier is based on excluding 'overlapping' mood criteria, such as psychomotor agitation, irritability and mood lability, among the most common features of mixed depression in our patients both with and without BPD. Although these symptoms may be non-specific, in view of the present authors and studies such as IMPACT (67), excluding them entirely from the diagnosis of mixed depressive states is not justified and may impair diagnostic sensitivity. Our results are in line with the clinical evidence that most of depressive mixed states are conditions of intense psychic suffering, where classical hypo/manic symptoms such as hyperactivity, euphoria or grandiosity are extremely rare (68).…”
Section: Discussionmentioning
confidence: 73%
“…However, the DSM system seems to lead nowhere over the foreseeing future. There may be small incremental improvements, such as the dimensional assessment of mixed states (14,15), but the questionable validity of the DSM constructs, along with the limited improvement as regards to their reliability (16), suggests that a shift in paradigm is necessary. This fact prompted a debate in United States between the American Psychiatric Association and the National Institute of Mental Health (NIMH) on the validity of DSM-5 and what were the alternatives, and the NIMH announced their proposal to fund research based on research domains criteria (RDoC), rather than DSM-5.…”
Section: Epidemiology and Diagnosismentioning
confidence: 99%